2020
DOI: 10.1111/jfbc.13587
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and antihypertensive properties of sesame seed enzymatic protein hydrolysate and ultrafiltration peptide fractions

Abstract: The objective of this study was to determine the in vitro antioxidant and antihypertensive potentials of sesame seed protein hydrolysate and its membrane ultrafiltration peptide fractions in comparison to the unhydrolyzed protein. Sesame seed protein isolate (SESPI) was prepared from the defatted sesame seed meal and then hydrolyzed using consecutive additions of pepsin and pancreatin to yield sesame protein hydrolysate (SESPH). The SESPH was subjected to membrane ultrafiltration consecutively to obtain fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 99 publications
3
32
1
Order By: Relevance
“…[29] With the exception of lysine, some of the values reported for the amino acid composition of the samples were higher when compared to the recommended allowance by WHO/FAO for some of the amino acids. results obtained further confirm work by earlier authors [13] that sesame protein hydrolyzates are rich sources of amino acids, such as the hydrophobic (HAA) and aromatic (AAA) amino acids which contributes to the antioxidant and renin-angiotensin system (RAS) inhibition activities.…”
Section: Amino Acid Compositionsupporting
confidence: 89%
See 2 more Smart Citations
“…[29] With the exception of lysine, some of the values reported for the amino acid composition of the samples were higher when compared to the recommended allowance by WHO/FAO for some of the amino acids. results obtained further confirm work by earlier authors [13] that sesame protein hydrolyzates are rich sources of amino acids, such as the hydrophobic (HAA) and aromatic (AAA) amino acids which contributes to the antioxidant and renin-angiotensin system (RAS) inhibition activities.…”
Section: Amino Acid Compositionsupporting
confidence: 89%
“…Hence, inhibiting the angiotensin converting and renin enzymes is a good approach to manage hypertension and other cardiovascular diseases . [13,43,44] As indicated in Figure 6, albumin fraction (30.03%) exhibited significantly (p < .05) greater ACEinhibitory activity than the other samples, a pattern which was in line with the trend of some amino acids, such as aspartic amino acid, serine and lysine (Table 1). The defatted flour (21.21%) and protein isolate (21.23%) also exhibited appreciable ACE-inhibitory activities, which were not significantly (p < .05) different from each other.…”
Section: Angiotensin and Renin Inhibitory Activitiessupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, the results confirmed that the <1 kDa membrane fraction (100 mg/kg weight), when orally administered to spontaneously hypertensive rats, decreased (−35 mmHg) the SBP [92]. A recent study by Aondona et al [93] assessed the in vitro antihypertensive potential of sesame seed protein hydrolysate and its fractionated peptides. The sesame seed protein hydrolysate was formed by using pepsin and pancreatin and then filtered through membrane ultrafiltration in order to obtain different peptide size fractions.…”
Section: Antihypertensive Activitymentioning
confidence: 56%
“…Statistical databases of FAO also indicated that India, Myanmar and China are the biggest sesame seed producers in the world (Myint et al, 2020) Overall, 97% of the sesame seed is supplied by Asia and Africa. Sesame seed is rich in various types of nutrients and bioactive compounds, making it a valuable oilseed (Aondona et al, 2021). According to different studies, sesame seed contains between 15% and 25% of protein, depending on the genotype (Yasothai, 2014;Parsaeian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%